ANALYSIS OF THE TREATMENT OF TEXTUAL PRODUCTION IN THE PORTUGUESE LANGUAGE BOOK FOR THE 9th YEAR OF ELEMENTARY SCHOOL - Fernandes Soares, Maria (Revista Gênero e Interdisciplinaridade, 2021)
This study aimed to analyze how textual production is given in a textbook from the 9th grade of elementary school, identifying which language concept is present in this topic. In the 9th year it is expected that the student has already developed a critical sense and one of the ways to materialize it is through textual production. Thus, it is expected that the texts produced by them make sense to those who read them and become part of the construction of the world of speakers and interlocutors. The textbook is an element present in the classroom, and for this reason it was the object of analysis in this article. By mapping the units of the copy, it is possible to observe how the textual production proposals are arranged, the textual genres to be produced and the guidelines on how to produce them. The analyzes had as theoretical basis the concepts of what is text presented by Marcuschi (2008) and Medeiros (2008). The concepts of language discussed by Brasil (1998), Geraldi (2011) and Travaglia (1996). The third conception that treats language as interaction was also the basis, in particular. In the methodology, qualitative analysis was used because it values ​​the quality of the object and not numerical values ​​discussed by Flick (2009), as well as the documental analysis by the authors Lüdke and André (2012), because the textbook is considered a document.